2021
DOI: 10.1016/s2468-1253(20)30296-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of surgical or endoscopic treatment of idiopathic achalasia: a systematic review and network meta-analysis

Abstract: This is a repository copy of Efficacy of surgical or endoscopic treatment of idiopathic achalasia: a systematic review and network meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 52 publications
(80 reference statements)
1
46
0
4
Order By: Relevance
“…42 Two recent network meta-analysis showed LHM and POEM having comparable efficacy overall with achalasia, and PD as performing less successfully. 43,44 Recent national society guidelines have suggested that LHM, PD, and POEM are effective treatment options for type I and type II achalasia, with a preference for a tailored and longer myotomy for type III achalasia. 45,46 As the ability for HRM to subtype achalasia continues to evolve, the potential for tailoring treatment for each patient with this disease will undoubtedly advance as well.…”
Section: Clinical Considerations and Therapeutic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Two recent network meta-analysis showed LHM and POEM having comparable efficacy overall with achalasia, and PD as performing less successfully. 43,44 Recent national society guidelines have suggested that LHM, PD, and POEM are effective treatment options for type I and type II achalasia, with a preference for a tailored and longer myotomy for type III achalasia. 45,46 As the ability for HRM to subtype achalasia continues to evolve, the potential for tailoring treatment for each patient with this disease will undoubtedly advance as well.…”
Section: Clinical Considerations and Therapeutic Optionsmentioning
confidence: 99%
“…A meta‐analysis has also revealed POEM to have a higher instance of gastroesophageal reflux disease (GERD) metrics than LHM, which is typically combined with a Dor or Toupet fundoplication 42 . Two recent network meta‐analysis showed LHM and POEM having comparable efficacy overall with achalasia, and PD as performing less successfully 43,44 …”
Section: Additional Considerationsmentioning
confidence: 99%
“…2 Currently, treatment failure rates are estimated in the range of 20-25% after endoscopic PD and 10-20% after laparoscopic HM. [3][4][5][6][7] Symptom recurrence after PD is related to lack of uniform protocols, operator's experience, and patient related factors. Recognized causes of surgical failure are an incomplete distal myotomy, twisting or mediastinal herniation of the fundoplication, reflux esophagitis, late fibrosis at the myotomy site, and dolichomegaesophagus.…”
Section: Introductionmentioning
confidence: 99%
“…With over a decade of experience and robust data showing excellent safety and efficacy, peroral endoscopic myotomy (POEM) is now considered as the first line treatment for achalasia cardia. 1 Around 10% of patients with prolonged duration of disease develop advanced achalasia cardia where there can be either excessive dilatation of the esophagus (megaesophagus with diameter > 6 cm) or the axis of the esophagus becomes tortuous taking shape of sigmoid (like sigmoid colon) or both. 2 , 3 Traditionally, esophagectomy has been considered the treatment option for this patient cohort, however, it is fraught with high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%